Optimization design of the cumulative sum (CUSUM) control chart - Magdalena Lucia Ginting (2009)
This project proposed the optimization design of the Cumulative Sum (CUSUM) control chart by finding the minimum value of the loss function L value. It is achieved by optimizing two of the CUSUM parameters: sample size n and reference value k.